(untitled) (PerCursos, 2023)
This article aims to investigate the tension between the degree and training in the current scenario of the Stricto Sensu Post-Graduation. Immersing in the context of teacher training, especially for issues involving personal and social issues. The study focuses on pursuing the following questions: How do the concepts of degree and training intertwine in the perception of stricto sensu graduate students? And what are the tensions that emerge in the realization of a master’s or doctorate? It is an exploratory, bibliographical and empirical research anchored in the hermeneutic analytical method. Based on the study carried out, it is concluded that there is a difference between training and qualifications, as the training process is broad, requires reflection, criticality and, above all, the ability to humanize oneself with education. The degree is essential for the job market, but it needs to be aligned with the development of responsible, democratic knowledge and committed to the social context.